2009
DOI: 10.1073/pnas.0906145106
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray tomography of phenotypic switching and the cellular response to antifungal peptoids in Candida albicans

Abstract: The opportunistic pathogen Candida albicans can undergo phenotypic switching between a benign, unicellular phenotype and an invasive, multicellular form that causes candidiasis. Increasingly, strains of Candida are becoming resistant to antifungal drugs, making the treatment of candidiasis difficult, especially in immunocompromised or critically ill patients. Consequently, there is a pressing need to develop new drugs that circumvent fungal drugresistance mechanisms. In this work we used soft X-ray tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
115
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 43 publications
1
115
0
Order By: Relevance
“…Most work performed on SXT microscopes addresses samples a few microns thick [4,[12][13][14][15][16][17][18]. Depending on the ratio between the sample thickness and the DOF, standard reconstruction algorithms introduce different artifacts which can be better estimated once the experimental DOF is known [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most work performed on SXT microscopes addresses samples a few microns thick [4,[12][13][14][15][16][17][18]. Depending on the ratio between the sample thickness and the DOF, standard reconstruction algorithms introduce different artifacts which can be better estimated once the experimental DOF is known [19].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Although there are significant studies on antibacterial peptoids, 16−21 little research has been performed using peptoids as therapeutic agents against fungi. Nonetheless, studies have successfully demonstrated that peptoids may be used against some fungal pathogens such as Candida albicans, 22 Fusarium virguliforme, and Fusarium lateritium. 23 The need in this field of research is for the rapid identification of antifungal peptoids via high-throughput screening of combinatorial libraries.…”
mentioning
confidence: 99%
“…Fresnel zone plates replace the condenser and/or objective lenses known from conventional visible light microscopy. This method allows for very high resolution in the soft x-ray spectral range down to 12-15 nm in two-dimensional imaging [1] and of 50 nm in three-dimensional imaging (tomography) [2]. The resolution is not limited by the short x-ray wavelength (nm-to-Å range) but by the focusing properties of the respective optics.…”
Section: Introductionmentioning
confidence: 99%
“…By application of a support constraint in the exit plane of the two crossed waveguide with a cross section of S = 150 × 150 nm 2 (smoothed by an error function), the near-field intensity in a virtual plane behind the two crossed waveguide can be retrieved iteratively in intensity and phase. Fig.…”
Section: Near-field Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation